Trends in Electronic Word of Mouth Research : A Bibliometric Review and Analysis - Mahadevan, Kala; Joshi, Sujata (Indian Journal of Marketing, 2021)
This aim of this paper was to evaluate the research literature on electronic word of mouth (EWOM) by conducting a bibliometric analysis of research papers in the Scopus database both from a global as well as an Indian perspective. The bibliometric review and analysis were carried out using the analytical tools of the Scopus database and Biblioshiny – the shiny interface of the bibliometric tool Bibliometrix. The research literature was investigated over a period of 10 years (2009 – 2019) and analyzed trends in production of research papers, citation trends, top countries, journals, and authors contributing to literature related to EWOM. USA was the topmost contributing country based on the number of publications and citations received. We observed that significant research on EWOM has been conducted in the Asian subcontinent by China, Taiwan, and Hong Kong. The key theories used in researching the domain of electronic word of mouth included the cognitive dissonance theory, the information adoption model, elaboration likelihood model, attribution theory, and the social exchange theory. The intellectual structure of the research on electronic word of mouth was studied in order to offer fundamental insights into recent developments in this research area, which would provide researchers and academicians with a broad guideline for conducting further research in this area.